The Role of Governance in Combating Administrative Corruption in Lebanon - Rania Adada (International Journal of Law Research and Studies, 2026)
Governance plays a vital role in combating administrative corruption in Lebanon by promoting transparency, accountability, integrity, and the rule of law. It provides institutional frameworks that support effective decision-making, performance evaluation, and public oversight, thereby strengthening public trust and improving the efficiency of public administration. Nevertheless, the implementation of governance principles continues to face significant challenges due to Lebanon’s complex political and administrative environment. This study examines the role of governance in combating administrative corruption in Lebanon and identifies the mechanisms required to enhance integrity and transparency within public institutions. The findings reveal that effective governance improves institutional performance by establishing clear organizational structures, reinforcing accountability, and ensuring transparent administrative processes, enabling institutions to achieve their objectives more efficiently. The study concludes that strengthening governance is essential for reducing administrative corruption and promoting sustainable institutional reform. It recommends reinforcing the legal framework, empowering independent oversight bodies, developing effective performance evaluation systems, and increasing public awareness and community participation to support transparency, accountability, and good governance.